JUDGE'S INTERPRETATION (STUDY ON THE CRIMINAL ACTION OF INSULTING TO THE HEAD OF STATE AND VICE HEAD OF STATE) - Prasetyo Utomo, Widhi; Kelik Wardiono; Nuria Siswi Enggarani (Awang Long Law Review, 2022)
This study aims to find out the judge's discovery of the criminal act of maltreatment against the Head of State and Deputy Head of State and the ideal concept of confiscating judges for the criminal act of maltreatment against the Head of State and Deputy Head of State. The research method uses a doctrinal approach in the form of normative juridical. Sources of data consist of secondary data, namely library materials and primary data in the form of statements from related parties. Methods of data collection through library research and interviews, then analyzed using qualitative normative methods. The results of the study show that the Panel of Judges in adjudicating cases related to criminal offenses against the Head of State and Deputy Head of State considers the elements contained therein which are stated to be involved have fulfilled the element of intent in committing a crime in accordance with the disclosure of the facts in the dispute, will but the panel of judges should in convicting and linking the article not only normatively, but also consider elements of other laws and regulations, so that the elements contained in the article governing the Head of State and Deputy Head of State can be refuted, because this is a citizen's constitutional right to freedom of expression in conveying criticism, suggestions and opinions to the authorities in order to create a better system. Meanwhile, the ideal concept in detaining judges for the crime of mistreatment of Heads of State and Deputy Heads of State is sociological or theological detention, where the law is placed in society so that its application is in line with people's lives based on the principle of justice.